2012
DOI: 10.1073/pnas.1117508109
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of heavily calcified coccolithophores at low CaCO 3 saturation during winter in the Bay of Biscay

Abstract: Coccolithophores are an important component of the Earth system, and, as calcifiers, their possible susceptibility to ocean acidification is of major concern. Laboratory studies at enhanced pCO 2 levels have produced divergent results without overall consensus. However, it has been predicted from these studies that, although calcification may not be depressed in all species, acidification will produce "a transition in dominance from more to less heavily calcified coccolithophores" [Ridgwell A, et al., (2009) B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 44 publications
8
77
4
1
Order By: Relevance
“…This contrasts with other studies where variability in coccolithophore dynamics across pH or C gradients (e.g. Charalampopoulou et al, 2011;Smith et al, 2012;Poulton et al, 2011Poulton et al, , 2013 are associated with co-varying gradients in growth-limiting factors such as temperature, nutrient concentrations and light availability. This contrast in coccolithophore response to pH or C , between gradients where carbonate chemistry covaries with other environmental parameters and gradients where there is no co-variability implies that any correlation between pH or C and coccolithophore dynamics along environmental gradients should be viewed with caution and in the context of any naturally occurring co-correlation with nutrient and light availability.…”
Section: Coccolithophore Calcification In Relation To Carbonate Chemicontrasting
confidence: 52%
“…This contrasts with other studies where variability in coccolithophore dynamics across pH or C gradients (e.g. Charalampopoulou et al, 2011;Smith et al, 2012;Poulton et al, 2011Poulton et al, , 2013 are associated with co-varying gradients in growth-limiting factors such as temperature, nutrient concentrations and light availability. This contrast in coccolithophore response to pH or C , between gradients where carbonate chemistry covaries with other environmental parameters and gradients where there is no co-variability implies that any correlation between pH or C and coccolithophore dynamics along environmental gradients should be viewed with caution and in the context of any naturally occurring co-correlation with nutrient and light availability.…”
Section: Coccolithophore Calcification In Relation To Carbonate Chemicontrasting
confidence: 52%
“…Smith et al, 2012;Meier et al, 2014). SEM analysis of the sediment trap samples revealed that only morphotype B/C, as described by Young et al (2003), thrives in the AZ-S waters south of Tasmania.…”
Section: Seasonal Variability In Coccolith Calcificationmentioning
confidence: 99%
“…On the other hand, ballasting by carbonates appears to increase the transfer of organic carbon to the ocean interior (Armstrong et al, 2002;Klaas and Archer, 2002). On seasonal timescales the counter pump contribution dominates (Boyd and Trull, 2007), but more complex interactions can occur over longer timescales as a result of changing extents of carbonate dissolution in sediments, including the possibility that enhanced calcite dissolution in the Southern Ocean contributed to lower atmospheric CO 2 levels during glacial maxima (Archer and Maier-Reimer, 1994;Sigman and Boyle, 2000;Ridgwell and Zeebe, 2005).…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because salinity, temperature, and light vary with carbonate saturation in these two seas it is difficult to disentangle the effects of these potentially confounding factors. Other studies have highlighted the complexity of decoupling multiple environmental changes on coccolithophore calcification (e.g., Smith et al, 2009;Horigome et al, 2014).…”
Section: Introductionmentioning
confidence: 99%